Effets de la crise de l’énergie sur la croissance économique de Montréal et du Québec - Martin, Fernand (L'Actualité économique, 1974)
AbstractThis impact depends upon changes in trends of certain economic activities both in the short and long run.In the short run the impact will be different in Canada as compared to the United States. The presence of a large hydro-electric capacity will ease the impact of the crisis. Yet, the federal government intervention in the level of oil prices and in the construction of the Sarnia-Montréal pipe-line introduces enough uncertainty to postpone many investment decisions in the Montreal petrochemical complex.In the long run some substitution is possible among sources of energy. In this respect the future Bay James hydro-electrical project should endow the Province of Quebec with a locational advantage, at least in the case of some industries.On the other hand, under the hypothesis that the price of foreign oil will remain high, Montreal looses one of its advantages: the access to cheap oil. This coupled with the fact that the petrochemical industries, e.g., those linked to secondary refining processes such as cracking, reforming and alkylation, prefer a location near the market, will in the long run reduce the rate of growth of the petrochemical complex near Montreal. The market forces are so strong that even before the crisis, Montreal, from 1960 to 1973, experienced a gradual weakening of its relative importance in the secondary stages of refining; for instance in alkylation its position went from 57.3 p.c. of total Canadian capacity to 16.8 p.c.If the hydro-electric potential is not used by the Province of Quebec as a development tool, the oil crisis will slightly hurt Montreal's prospects for development.